MODE OF ACTION OF AMRITADYA GUGGULU IN THE MANAGEMENT OF STHOULYA W.S.R TO OBESITY - Raina, Triveni; Saini, Swapnil; Sharma, Dalip (International Journal of Ayurveda and Pharma Research, 2018)
Obesity (Sthoulya) is the major and basic cause of lifestyle disorders like Diabetes mellitus (T2DM), Coronary heart disease (CHD), Hypertension. Obesity (Sthaulya) is increasing at an alarming rate in developed industrialized countries which are undergoing rapid nutrition and lifestyle transition. Obesity is one of the most effective diseases which affect someone’s social, physical and mental status. In Ayurveda, Sthoulya (Obesity) is regarded as Medoroga, a disorder of Meda Dhatu, which includes fat tissue and fat metabolism. According to Ayurveda, Sthoulya begins with an imbalance of Doshas (Vata, Pitta and Kapha), Agni (digestive fire), Malas (waste products) or an imbalance of Srotas (microcirculatory channels). This collection of imbalances then interferes with the formation of tissues or Dhatus and leads to a tissue imbalance that we experience as excess weight. Overweight and obesity are linked to more deaths worldwide than underweight. Overall, about 13% of the world adult population (11% of men and 15% of women) was obese in 2016. The worldwide prevalence of obesity nearly tripled between 1975 and 2016. Amritadya Guggulu possesses Rasa- Katu, Tikta, Kashaya, Guna- Laghu, Ruksha and Virya- Ushna, Vipaka- Katu, Dosha Karma- Kapha Vatashamaka is effective in the management of Sthoulya. By virtue of its Rasapanchaka, contents of drug are very well indicated in Kapha predominant pathologies. Due to this property, it breaks the Samprapti of Sthoulya. Hence the present attempt is done to encompass the up to date comprehensive literature to study the mode of action of Amritadya Guggulu in the management of Sthoulya w.s.r. to Ayurvedic properties and modern pharmacology.